COMPREHENSIVE REVIEW ON THE IMPACT OF PHARMACISTS ON MEDICATION SAFETY AND ADHERENCE - SarranMahdi Hassan Alyami, Hamad Mohammed Misfer Al Rizq, Nasser Mohammed N Lasloom, Hadi Mohammad Mahdi Alamri, Mubarak MaraiHadiAlAmer, JaberHadiMarzookLasloom, HadiMnasar H Alyami, Mahdi Abdullah M Alzhoof, MeshaalMesferAiedAlRazq (Chelonian Research Foundation, 2023)
Medication safety and compliance are imperative perspectives of healthcare and affect understanding results and healthcare costs. pharmacists play a crucial part in guaranteeing that drugs are secure and supporting compliance with an assortment of intercessions. This orderly audit draws on existing information to assess drug effect lists' effect on medicine utilization and adherence. Key mediations incorporate pharmacotherapy, persistent instruction, clinical administration, and shared commitment. Strategies such as writing surveys are utilized to recognize essential considerations. Pharmacists’ mediation successfully moves medicine security and adherence to treatment over numerous settings and patients. In any case, issues such as restricted assets and the need for integration into the treatment group stay. The dialog emphasized the significance of collaborative endeavors and the requirement for more investigation to move forward with physician-led intercessions. In summary, pharmacists are critical partners in progressing pharmaceutical security and compliance, and this article offers suggestions to maximize the impact on well-being. Key words: Pharmacists, medication safety, medication adherence, interventions, systematic review